Pashto-English codeswitching: Testing the morphosyntactic constraints of the MLF model - Khan, Arshad Ali; Khalid, Amina (Lingua, 2018)
•The present study empirically supports the Differential Access Hypothesis.•The early system morphemes are salient in the production process.•The late system morphemes are triggered at the level of formulator.•Pashto is the matrix language responsible for the morphosyntactic frame.•The outsider system morphemes are responsible to mark tense, aspect and agreement. This study examines the morphosyntactic constraints on Pashto-English codeswitching. The framework for the present research is based on the widely attested code-switching model, the Matrix Language Frame (MLF) Model and 4-M model (Myers-Scotton and Jake, 2000, 2009). In order to investigate these constraints, 25 clips from the Pashto speech community have been transcribed and analyzed. The two constraints, the Morpheme Order (MO) constraint and the System Morpheme (SM) constraint of MLF Model are supported by the data. The Pashto-English bilingual data empirically support Myers-Scotton Matrix Language Frame Model and 4-M model (1993, 2002, 2009) and in the entire data set, not a single counter example has been recorded. The present study supports the idea that Pashto-English bilingual data is asymmetrical in structure, where English is the Embedded Language (EL) and Pashto is the Matrix Language (ML) responsible for the well-formedness and morphosyntactic frame. The study reveals that the subject-verb agreement, morpheme order, and the late system morpheme (bridge, outsider) play a crucial role to maintain the morphosyntactic frame of the Pashto language. The study validates the Differential Access Hypothesis (Myers-Scotton, 2002, 2006; Myers-Scotton and Jake, 2009) in that the late system morphemes are triggered at the threshold level in order to uphold the structure.